Implementasi PjBL Berbasis Media Digital untuk Meningkatkan Numerasi dan Pemahaman Konsep Bilangan Cacah Siswa Kelas V: Implementation of Digital Media-Based PjBL to Improve Numeracy and Understanding of Whole Number Concepts in Grade V Students - Larno Larno; Aryo Andri Nugroho; Fenny Roshayanti (ITScience (Information Technology and Science), 2026)
Mathematics instruction on the concept of whole numbers in elementary schools is still dominated by conventional, teacher-centered methods, resulting in low student engagement and affecting numeracy skills and learning outcomes. This study aims to analyze the effect of implementing the Project-Based Learning (Pjbl) model, assisted by interactive digital media, on students' numeracy skills and learning outcomes. The study used a mixed-methods approach with a nonequivalent control-group experimental design. The research subjects consisted of fifth-grade students from Ulin Nuha Wuryantoro Elementary School (experimental group) and Wuryantoro 1 Elementary School (control group). Data collection techniques included tests, observations, questionnaires, and interviews. Quantitative data analysis included normality and homogeneity tests, and independent-samples t-tests using SPSS, while qualitative data were analyzed descriptively. The study found a significant difference between the two groups. The average numeracy score of students in the experimental group was higher than that of the control group (33.10 > 24.13). Similarly, the mathematics learning outcomes, the experimental group obtained a higher average score (80.95 > 75.63). The hypothesis test yielded a p-value < 0.05, indicating a significant effect of implementing interactive digital media-assisted PJBL on students' numeracy skills and learning outcomes. Thus, the interactive digital media-assisted PJBL model effectively improves the quality of mathematics learning, particularly in whole numbers, and encourages active student involvement in the learning process.